Longitudinal Transition Patterns of Peer Attachment and Parent-Child Relationships among High School Students. - Gao, Tingting; Liang, Leilei; Su, Yingying; Li, Muzi; Mei, Songli; Zhou, Chengchao; Meng, Xiangfei (Journal of Child & Family Studies, 2024)
This study aimed to explore the latent profiles of peer attachment and parent-child relationships and longitudinal transition patterns for within-person and within-sample profiles among a cohort of high school students. A cohort of 453 participants from China completed the above-mentioned measures with a six-month interval from grade 10 to 11. This study included 64.0% girls and 36.0% boys. Latent profile analysis (LPA) was used to explore the distinct profiles reflecting different response patterns for peer attachment and parent-child relationships at each time point. Latent transition analysis (LTA) was adopted to examine the membership of distinct latent profiles and how individuals move between profiles over time. Three latent profiles were identified with poor, moderate and good peer attachment and parent-child relationships. The stability of the same profile ranged from 0.601 to 0.803. The lowest transition probability was found between the poor and good profiles, whereas a higher transition probability from the poor and good profiles to the moderate profile was demonstrated. Patterns of peer attachment and parent-child relationships were associated with depression, anxiety, and Internet addiction (IA). This study advanced the knowledge of the heterogeneity and variation in peer attachment and parent-child relationships by a person-centered approach in a longitudinal study. The findings of the study direct selective interventions to populations with poor attachment and parent-peer relationships, and transitions from good to poor attachment direction across latent profiles of attachment and parent-peer relationships. Establishing secure attachment with peers and having good parent-child relationships may contribute to good adolescents' mental health and protect them from excessive Internet use. Highlights: There were three distinct profiles of peer attachment and parent-child relationships in a cohort of high school students. These identified profiles were transient between two measurement waves. Profiles of peer attachment and parent-child relationships were associated with depression, anxiety, and Internet addiction (IA).